You belong here the power of being seen, heard, and valued on your own terms - Dabbs, Kim (Ascent Audio, 2024)
Everyone feels like an outsider at some point in their life-when we walk into a room and think to ourselves, "I don't belong here." To avoid these feelings of exclusion, many of us hide our authentic selves and allow others to define our identity. You Belong Here offers a new framework that allows each of us to define how we want to be seen, heard, and valued on our own terms so we feel a sense of belonging in any situation. Further, it serves as a launchpad for organizational leaders and culture builders to create safe spaces for individuals to show up as their authentic selves. Listeners will explore our four identities: Our Lived Identity is made up of the aspects of our identity we inherit when we are born into the world. Our Learned Identity includes the parts of our identity that we've chosen or claimed as we make our way through the world. Our Lingering Identity is the identity we default to when we feel like an outsider and fall back into as a survival mechanism. Our Loved Identity is where we find our authentic selves. In the journey to understand our past experiences and how society has established barriers to entry, we can design our own future. We learn to rewrite the stories that aren't serving us and embrace the ones that do. Rather than look for a seat at someone else's table, we find the tools to build our own.